The Effects of Macroeconomics, Oil Prices, and Competitive Resources on LQ 45 Stock Returns - Garnia, Erna; Riadi, Deden Rizal; Tahmat, Tahmat; Lisaumi, Siti Riyyan (Husnayain Business Review, 2024)
The capital market is a component of a country's financial system that accommodates meetings between parties who need funds and parties who have funds on the Indonesia Stock Exchange. The expected returns of investors in the Indonesia Stock Exchange can be influenced by various macro factors, including macroeconomics, world oil prices, and competitiveness. Macro factors are related to the president in terms of economic policies, regulations, and capital market stability. LQ 45 which is an index consisting of liquid stocks, is used as a reference for setting investment strategies. This study aims to determine the effect of the three macro factors, namely macroeconomics, world oil prices, and competitiveness on LQ 45 returns during the last two terms president of the Indonesian, Susilo Bambang Yudhoyono and Joko Widodo, using regression analysis. Analysis of each term of office is divided into high return and low return groups. The data in this study used monthly data from October 2004 to October 2021. The results showed that the three macro factors simultaneously affected the LQ 45 stock return group. Partially, it shows that world oils have a positive effect on high and low returns, both during the presidential of Susilo Bambang Yudhoyono and Joko Widodo. Macroeconomics and Competitive Resources show varied results in influencing LQ 45 returns.